2015
DOI: 10.1080/07399332.2015.1103739
|View full text |Cite
|
Sign up to set email alerts
|

“Will I ever be a true woman?” An exploration of the experiences of women with vestibulodynia

Abstract: In this study we explored the experiences of Norwegian women living with vestibulodynia, a chronic disease affecting young women all over the world. Using a phenomenological approach we conducted in-depth interviews with eight women who had struggled with vestibulodynia for several years. Our findings reveal that their efforts to fulfill their partners' sexual desires as well as their own represented an encompassing ongoing process. In addition, we highlight the interrelationship between the intensity of vulva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Previous qualitative studies have shown that PVD can have a significant negative impact on a woman`s self-esteem (Ayling and Ussher, 2008;Connor et al, 2008;Groven, Råheim, Håkonsen and Haugstad, 2015;Sadownik et al, 2012). Studies have reported that a woman`s sexual function and behaviour have a significant relationship with her genital self-image (Herbenick et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Previous qualitative studies have shown that PVD can have a significant negative impact on a woman`s self-esteem (Ayling and Ussher, 2008;Connor et al, 2008;Groven, Råheim, Håkonsen and Haugstad, 2015;Sadownik et al, 2012). Studies have reported that a woman`s sexual function and behaviour have a significant relationship with her genital self-image (Herbenick et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…University Hospital, Norway, in an attempt to alleviate the burden of longstanding pelvic and gynecological pains (19)(20)(21). In recent years, SCT has been modi ed and further developed to treat women with PVD, based on experiences from a pilot study (22), from PVD patients (23) and physiotherapy students treating PVD patients (24). Whereas multimodal physiotherapy treatments are usually provided by physiotherapists specialized in women's health, SCT is intended to be implemented in primary care and designed to be easy to learn.…”
Section: Somatocognitive Therapy (Sct) Is An Existing Multimodal Physiotherapy Intervention Developed At Oslomentioning
confidence: 99%
“…These women experience vulvar pain through direct touch, such as sexual intercourse, tampon insertion or physical examination. Most women with vulvodynia complain of pain during sexual activities (dyspareunia) or of inability to have intercourse due to pain . Localised, provoked vulvodynia is often associated with vaginismus: involuntary spasms of the pelvic floor muscles provoked by touch, which narrow or close the vaginal opening .…”
Section: Introductionmentioning
confidence: 99%
“…Women with vulvodynia have reported a reduced quality of life, including anxiety and depression, as well as feelings of shame and guilt regarding the pain in their genital area . Because women with vulvodynia have challenges with or are unable to perform penetrative vaginal intercourse, they describe themselves as fake or inauthentic women, and as incomplete girlfriends or wives . Indeed, vulvodynia is reflected in couple's relationships.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation